2021
DOI: 10.2196/15708
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Natural Language Processing in Mental Health: Systematic Review

Abstract: Background Machine learning systems are part of the field of artificial intelligence that automatically learn models from data to make better decisions. Natural language processing (NLP), by using corpora and learning approaches, provides good performance in statistical tasks, such as text classification or sentiment mining. Objective The primary aim of this systematic review was to summarize and characterize, in methodological and technical terms, stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(128 citation statements)
references
References 104 publications
(156 reference statements)
5
122
0
1
Order By: Relevance
“…In Supplementary Table S1 , we have complied recent review articles detailing emerging examples of how statistical and ML methods are being utilized for clinical outcome prediction in major medical specialities. Applications are found in the fields of Anesthesiology [ 32 , 33 , 34 ], Dermatology [ 35 , 36 , 37 ], Emergency Medicine [ 38 , 39 ], Family Medicine [ 40 , 40 ], Internal Medicine [ 41 , 42 , 43 ], Interventional Radiology [ 44 , 45 ], Medical Genetics [ 46 ], Neurological Surgery [ 47 ], Neurology [ 48 , 49 , 50 ], Obstetrics and Gynecology [ 51 , 52 ], Ophthalmology [ 53 , 54 , 55 ], Orthopaedic Surgery [ 56 ], Otorhinolaryngology [ 57 , 58 ], Pathology [ 59 , 60 , 61 ], Pediatrics [ 62 ], Physical Medicine and Rehabilitation [ 63 , 64 ], Plastic and Reconstructive Surgery [ 65 , 66 ], Psychiatry [ 67 , 68 ], Radiation Oncology [ 69 , 70 ], Radiology [ 71 , 72 ], General Surgery [ 73 , 74 ], Cardiothoracic Surgery [ 75 , 76 ], Urology [ 77 , 78 ], Vascular Surgery [ 79 , 80 ]. These papers introduce terms describing ML models as ‘supervised’ or ‘unsupervised’.…”
Section: Emerging Methods and Emerging Applicationsmentioning
confidence: 99%
“…In Supplementary Table S1 , we have complied recent review articles detailing emerging examples of how statistical and ML methods are being utilized for clinical outcome prediction in major medical specialities. Applications are found in the fields of Anesthesiology [ 32 , 33 , 34 ], Dermatology [ 35 , 36 , 37 ], Emergency Medicine [ 38 , 39 ], Family Medicine [ 40 , 40 ], Internal Medicine [ 41 , 42 , 43 ], Interventional Radiology [ 44 , 45 ], Medical Genetics [ 46 ], Neurological Surgery [ 47 ], Neurology [ 48 , 49 , 50 ], Obstetrics and Gynecology [ 51 , 52 ], Ophthalmology [ 53 , 54 , 55 ], Orthopaedic Surgery [ 56 ], Otorhinolaryngology [ 57 , 58 ], Pathology [ 59 , 60 , 61 ], Pediatrics [ 62 ], Physical Medicine and Rehabilitation [ 63 , 64 ], Plastic and Reconstructive Surgery [ 65 , 66 ], Psychiatry [ 67 , 68 ], Radiation Oncology [ 69 , 70 ], Radiology [ 71 , 72 ], General Surgery [ 73 , 74 ], Cardiothoracic Surgery [ 75 , 76 ], Urology [ 77 , 78 ], Vascular Surgery [ 79 , 80 ]. These papers introduce terms describing ML models as ‘supervised’ or ‘unsupervised’.…”
Section: Emerging Methods and Emerging Applicationsmentioning
confidence: 99%
“…For instance, researchers have found that liberals tend to self-report less happiness than conservatives but display more in their actual behavior [15]. Lately, computer-based tools, such as Natural Language Processing (NLP) and Machine Learning (ML), have increasingly been adopted to study mental health [16]. Using large amounts of text from either patient records, emergency room data or even social media, researchers have been able to extract symptoms, classify the severity and identify psycho-pathological clues [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, computer-based tools, such as Natural Language Processing (NLP) and Machine Learning (ML), have increasingly been adopted to study mental health [16]. Using large amounts of text from either patient records, emergency room data or even social media, researchers have been able to extract symptoms, classify the severity and identify psycho-pathological clues [16]. NLP has even been used to design chat-bots for complementary mental health treatment [17].…”
Section: Introductionmentioning
confidence: 99%
“…The data from non-traditional digital mental health support services offers a unique window into mental health needs and experiences of distress, and provides an opportunity to evaluate personalised support approaches. In particular, big data analysis techniques, such as natural language processing (NLP) and machine learning, allow us to examine, at scale, expressions of distress and user interactions with mental health services ( 6 ). To date, the challenges involved in accessing relevant data sets have partly prevented a full exploration of the value of such techniques for mental health insights and service evaluation [see ( 7 ) for a notable exception].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of mental health, NLP has also been used for predicting suicidal ideation ( 17 , 18 ), analysing post-traumatic stress disorder ( 19 ), predicting psychosis ( 20 ) and other disorders ( 21 ), generating artificial mental health records ( 22 ), and for motivational interviewing ( 23 ). For a more complete review of NLP in mental health, see ( 6 ). However, NLP models have been rarely applied to digital mental health resources such as crisis text line services ( 7 ), and to date no published studies analyse the Shout data set.…”
Section: Introductionmentioning
confidence: 99%